The Site of Lead: Social Poisoning in El Salvador - De Burgos, Hugo (Anthropologica, 2015)
This article explores lead contamination, or plumbism, as both an illness and a symptom of social suffering caused by unscrupulous corporations operating with the complicity of corrupt governments and backed up by medical bad faith in El Salvador. I explore how the biomedical model of disease (as a quantifiable phenomenon) is used politically to contest and delegitimize victims of plumbism, privileging economic progress over human welfare. I examine the tensions between official narratives and people's narratives of illness and their relationship to an ideology of industrial development and economic prosperity in El Salvador.